2008
DOI: 10.1038/leu.2008.165
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic, pharmacodynamic and intracellular effects of PEG-asparaginase in newly diagnosed childhood acute lymphoblastic leukemia: results from a single agent window study

Abstract: L-asparaginase is an effective drug for treatment of children with acute lymphoblastic leukemia (ALL). The effectiveness is thought to result from depletion of asparagine in serum and cells. We investigated the clinical response in vivo of 1000 IU/m 2 pegylated (PEG)-asparaginase and its pharmacokinetic, pharmacodynamic and intracellular effects in children with newly diagnosed ALL before start of combination chemotherapy. The in vivo window response was significantly related to immunophenotype and genotype: 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 48 publications
1
70
0
Order By: Relevance
“…3,5,6 Indeed, a major limitation in the capacity to deliver the intended up-front asparaginase therapy is the high rate of occurrence of hypersensitivity reactions, frequently reported in as many as 30% of patients receiving E. coliderived asparaginase, but with reported rates as high as 70%. 1,3,[7][8][9] Allergic reaction symptoms range from local reactions at the site of intramuscular injection to severe systemic reactions including anaphylaxis, which can occur with intramuscular or intravenous administration. Also demonstrated has been the phenomenon of "silent inactivation," with the formation of neutralizing antibodies and reduced asparaginase activity in the absence of a clinically evident allergic reaction.…”
Section: Consensus Expert Recommendations For Identification and Manamentioning
confidence: 99%
See 1 more Smart Citation
“…3,5,6 Indeed, a major limitation in the capacity to deliver the intended up-front asparaginase therapy is the high rate of occurrence of hypersensitivity reactions, frequently reported in as many as 30% of patients receiving E. coliderived asparaginase, but with reported rates as high as 70%. 1,3,[7][8][9] Allergic reaction symptoms range from local reactions at the site of intramuscular injection to severe systemic reactions including anaphylaxis, which can occur with intramuscular or intravenous administration. Also demonstrated has been the phenomenon of "silent inactivation," with the formation of neutralizing antibodies and reduced asparaginase activity in the absence of a clinically evident allergic reaction.…”
Section: Consensus Expert Recommendations For Identification and Manamentioning
confidence: 99%
“…18 This cut-off of ≥ 0.1 IU/mL has been confirmed and used in many clinical trials. 9,19,[22][23][24] The question arises whether a lower threshold, for example of 0.05 IU/mL, also leads to complete asparagine depletion. Rizzari and colleagues showed that trough asparaginase activity levels of < 0.05 IU/mL, obtained either with native E. Coli or Erwinia asparaginase, resulted in serum and CSF asparagine depletion in children with ALL.…”
Section: What Defines Optimal Asparaginase Activity?mentioning
confidence: 99%
“…23 Results of the pharmacokinetic and dynamic studies of vincristine and PEG-asparaginase given upfront before start of the combination chemotherapy are published elsewhere. 14,15,16 Treatment results according to presenting features Tables 3-6 show the outcomes per study according to the NCI criteria. 20 In the BFM-based protocols ALL-7 and ALL-8, a poor outcome is related to NCI HR criteria, male gender (only ALL-8 study), T-lineage ALL and a high WBC.…”
Section: Tablementioning
confidence: 99%
“…Part of the patients were included in research projects that studied pharmacokinetics andFdynamics of one additional dose of vincristine 14 or PEG-asparaginase before start of therapy. 15,16 The treatment protocol for NHR patients was identical to the ALL-6. HR patients received several intensification elements on top of the NHR schedule: (a) Daunorubicin was added to the 3 drug induction.…”
Section: Patients and Treatmentmentioning
confidence: 99%
“…Previous studies have proposed that enzyme activities greater than 100 U/L ensure asparagine depletion in the serum and CSF [7,23,24]. An important prognostic milestone in ALL therapy is day of the end of induction therapy (day 33 on the BFM regimens) when the measurement of MRD (negative or not negative) and the randomization according to three different risk categories (SR, MR, HR) take place.…”
Section: Discussionmentioning
confidence: 99%